Remembering the rejection of Muhammad Ali: identity, civil rights and social memory. Issue 3 (3rd July 2018) - Townsend, Stephen; Phillips, Murray G.; Osmond, Gary
ABSTRACT: When Muhammad Ali died in June 2016, he was remembered by the media as a hero in the fight for racial equality. Tributes for the great boxer were meaningful in many respects, but they were also incomplete, sanitised and misleading. This paper aims to re-complicate our understanding of Ali's portrayals in the media by analysing newspaper discourse in the years immediately following his conversation to the Nation of Islam. Specifically, this investigation compares and contrasts the complex ways that black and white journalists used both his birth name (Cassius Clay) and his adopted name (Muhammad Ali) as a way of signalling their attitudes toward him. Close reading of newspaper articles published between March 1964 and September 1967 reveals that black journalists rejected Ali's adopted name and identity almost as comprehensively as their white colleagues. This aspect of Ali's legacy has been largely forgotten by the contemporary media, which calls us to consider the cultural construction of social memory, particularly when it revolves around sporting icons.